Criminal liability for crimes against national security - Polianskyi, Anton; Polianskyi, Oleh (Archives of Criminology and Forensic Sciences, 2021)
This research paper analyzes the current Legislation of Ukraine in the field of criminal liability for crimes against national security. It is noted that prevention of this type of crime is one of priorities of criminal law policy that aims to preserve national sovereignty and its independence proclaimed by the Constitution of Ukraine, as well as ensuring its economic and information security are the most important functions of the state. Scientific achievements of leading scientists in the field of criminal liability, crimes against national security are analyzed. Their work part changes or additions to relevant provisions of the Criminal Code of Ukraine has been studied. General scientific (dialectical, systemic) and specific scientific methods became research methods. Dialectical method made it possible to determine the general state and prospects of research on the legal regulation of criminal liability for crimes against national security. Using the system method that was used in the research process, system of legislation of the outlined issue is determined. While analysis of current regulations in force in Ukraine in the field of criminal liability for crimes against national security formal and legal methods were used. Definition by the Basic Law of the country of the most important functions of the state of the issue of protection of sovereignty and territorial integrity of Ukraine ensures this research relevance. Due to the threat posed by aggression in the east, that began in 2014, the crime rate is gaining momentum. The need for enhanced state control and the introduction of effective mechanisms, in terms of strengthening criminal liability for planned crimes is becoming urgent.